Analisis Yuridis Kepastian Hukum Hak Atas Tanah Melalui Program Pendaftaran Tanah Sistematis Lengkap (PTSL) di Indonesia - Atika Ayu; Siti Julaeha (Legis Nexus: Jurnal Ilmu Hukum, 2026)
This study aims to analyze the legal framework and effectiveness of the Complete Systematic Land Registration Program (Pendaftaran Tanah Sistematis Lengkap/PTSL) in ensuring legal certainty over land rights in Indonesia. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively through library research. The findings indicate that PTSL is an implementation of Article 19 of Law Number 5 of 1960 concerning Basic Agrarian Principles, supported by Government Regulation Number 24 of 1997 and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 6 of 2018. The program provides legal certainty through the issuance of land certificates as strong legal evidence of ownership while promoting orderly land administration and improving public welfare. Nevertheless, the implementation of PTSL still faces several challenges, including inconsistencies between physical and juridical land data, limited public legal awareness, insufficient human resources, and potential land disputes. Therefore, improving land data quality, strengthening supervision, accelerating the digitalization of land administration, and increasing public participation are essential to optimize the realization of legal certainty and legal protection over land rights